Acoustically stimulated phase transition and low temperature optical spectra in PbI2 crystal - Bilyi, M. M.; Gorban, I. S.; Dmitruk, I. M.; Salivonov, I. M.; Ostrovskii, I. V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
The influence of intensive ultrasonic wave on the crystal structure of PbI2 was investigated. Acoustically stimulated phase transition have been observed for the first time.